The biopsychosocial (BPS) model of dementia as a tool for clinical practice. A pilot study. (22nd January 2016) - Revolta, Catherine; Orrell, Martin; Spector, Aimee
ABSTRACT: Background: Equipping staff with the skills to provide high quality care in dementia is essential. The Biopsychosocial (BPS) model of dementia (Spector and Orrell, 2010) is a practical tool designed to encourage staff to develop personalized interventions and treatment plans for people with dementia. This feasibility study aimed to examine the impact of training staff to use the BPS model on skills of formulation, attitude towards dementia and sense of role competence. Method: A within-subjects design was used. Thirty-seven staff working in dementia care across a community mental health team (CMHT), inpatient wards, and residential care homes were trained to use the BPS model. Outcomes were measured at baseline, post-training, and four week follow-up. Results: The ability of staff to understand, formulate, and develop interventions for people with dementia increased significantly following training. There were small, non-significant improvements in positive attitudes, and sense of competence following training. Staff also reported that training improved their understanding of biological and psychosocial factors in dementia. Conclusions: This study provides preliminary evidence that training staff to use the BPS model can lead to improvements in their ability to understand and develop interventions for people with dementia. Further research would be required to draw firm conclusions about its effectiveness.